2018
DOI: 10.1210/jc.2017-01759
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Regulates Glycogen Synthesis in Human Endometrial Glands Through Increased GYS2

Abstract: We demonstrate that insulin, not progesterone, directly regulates glycogen synthesis through canonical acute inactivation of GSK3α/β and noncanonical stimulation of GYS2 transcription. Persistently elevated GS enables endometrium to synthesize glycogen constitutively, independent of short-term nutrient flux, during implantation and early pregnancy. This suggests that insulin plays a key, physiological role in endometrial glucose metabolism and underlines the need to delineate the effect of maternal obesity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 30 publications
3
8
0
Order By: Relevance
“…Detection of INSR in mink uterine GE and LE in vivo (Fig. 3) agrees with findings for horse (53), rat (45,46) and human (42,43,44). Although INSR was not detected in mink uterine stroma, the protein was expressed by the stroma of other species (54,55).…”
Section: Uterine Insr Protein During Estrus Diapause and Pregnancysupporting
confidence: 85%
See 2 more Smart Citations
“…Detection of INSR in mink uterine GE and LE in vivo (Fig. 3) agrees with findings for horse (53), rat (45,46) and human (42,43,44). Although INSR was not detected in mink uterine stroma, the protein was expressed by the stroma of other species (54,55).…”
Section: Uterine Insr Protein During Estrus Diapause and Pregnancysupporting
confidence: 85%
“…Because the hormone concentrations used by us were supraphysiological, it is worth noting that many investigators propose that high E 2 and/or P 4 concentrations contribute to insulin resistance and gestational diabetes mellitus (80,81,82). Flannery et al, (42) showed that while insulin increased glycogen content of primary human uterine epithelial cells, the hormone had no effect on the same cell type obtained from women taking oral contraceptives containing E 2 + P 4 . Nevertheless, treatment of GMMe cells with E 2 →P 4 (without insulin) caused a 2-fold increase in Insr expression when compared to cells treated with E 2 , P 4 or as controls (Fig.…”
Section: Insr Mrna Expression In Response To E 2 P 4 and Insulinmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the 5 genes have been implicated to be involved in cancers, including PCa. GYS2 encodes a protein that catalyzes the rate-limiting step in the synthesis of glycogen (39). It has been reported that GYS2 acted as a tumor suppressor in hepatocellular carcinoma (HCC) (40).…”
Section: Discussionmentioning
confidence: 99%
“…In diabetes mellitus, excessive plasma glucose concentrations can upregulate intestinal SGK1 expression and thus SGK1dependent stimulation of SGLT1, contributing to the maintenance of obesity (Dieter et al, 2004). A number of studies have proposed that abnormal glucose metabolism in the endometrium contributes to the increased risk of adverse pregnancy outcomes (Salker et al, 2017;Flannery et al, 2018;Raglan et al, 2020). It has now been reported, that SGLT1 is indeed expressed in the endometrium and controls glycogen accumulation essential for histiotrophic nutrition in pregnancy (Salker et al, 2017).…”
Section: Sgk1 Obesity and Diabetesmentioning
confidence: 99%